2004
DOI: 10.1111/j.1365-2044.2004.03967.x
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal intubation using the Bonfils intubation fibrescope after failed direct laryngoscopy*

Abstract: SummaryFailed tracheal intubation due to a difficult airway is an important cause of anaesthetic morbidity and mortality. This study was undertaken to evaluate the effectiveness of the Bonfils intubation fibrescope for tracheal intubation after failed direct laryngoscopy. Twenty-five patients undergoing coronary artery bypass grafting were enrolled in the study after two attempts at conventional laryngoscopy by a board certified anaesthetist had failed. Intubation with the Bonfils fibrescope was successful on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
46
0
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 12 publications
1
46
0
2
Order By: Relevance
“…However, in contrast to Bein et al, 7 who reported a 100% success rate in endotracheal intubation using the Bonfils intubation fiberscope, 7 success was achieved in 82% of patients in our study. In another investigation, Bein et al 6 observed that endotracheal intubation was successful in 96% of patients, when the Bonfils intubation fibrescope is used in patients with an unanticipated difficult airway, after direct laryngoscopy had failed. 6 The main reason for intubation failure with the Bonfils intubation fibrescope in our study was most likely due to an inability to direct the rigid device underneath the epiglottis, despite the application of external laryngeal pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, in contrast to Bein et al, 7 who reported a 100% success rate in endotracheal intubation using the Bonfils intubation fiberscope, 7 success was achieved in 82% of patients in our study. In another investigation, Bein et al 6 observed that endotracheal intubation was successful in 96% of patients, when the Bonfils intubation fibrescope is used in patients with an unanticipated difficult airway, after direct laryngoscopy had failed. 6 The main reason for intubation failure with the Bonfils intubation fibrescope in our study was most likely due to an inability to direct the rigid device underneath the epiglottis, despite the application of external laryngeal pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In another investigation, Bein et al 6 observed that endotracheal intubation was successful in 96% of patients, when the Bonfils intubation fibrescope is used in patients with an unanticipated difficult airway, after direct laryngoscopy had failed. 6 The main reason for intubation failure with the Bonfils intubation fibrescope in our study was most likely due to an inability to direct the rigid device underneath the epiglottis, despite the application of external laryngeal pressure. Since the patients' heads were fixed in a neutral position, it remains speculative as to whether or not endotracheal intubation would have been successful with a certain degree of atlantooccipital joint mobility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Devices such as the Bonfils intubation fibrescope and the Shikani Optical stylet have been available for clinical use for a number of years. Although there are case reports and case series documenting efficacy of these devices in management of both routine and difficult airways [3,5,17,[25][26][27][28][29], large comparative studies assessing their efficacy compared with alternative airway devices are lacking. Two studies [30,31] have compared the optical scopes (LFPS and the Shikani optical stylet) with the bougie.…”
Section: ó 2007 the Authorsmentioning
confidence: 99%
“…Rigid intubation endoscopes represent one alternative for intubation of unexpected difficult airways [44,45]. In order to successfully employ these instruments in emergency situations, sufficient experience is needed in patients with a normal airway [46].…”
Section: Rigid Intubation Endoscopesmentioning
confidence: 99%